2011
DOI: 10.1007/s10995-011-0856-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Association of Biomedical, Psychosocial and Behavioral Risks with Adverse Pregnancy Outcomes Among African-Americans in Washington, DC

Abstract: Objectives This study investigates the relationship between diabetes, hypertension, preeclampsia, and Body Mass Index (BMI) -- the most common and interrelated medical conditions occurring during pregnancy; sociodemographic and behavioral risk factors; and adverse pregnancy outcomes in high-risk urban African American women in Washington, DC. Methods Data are from a randomized controlled trial conducted in 6 prenatal clinics. Women in their 1st or 2nd trimester were screened for behavioral risks (smoking, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 33 publications
3
34
1
Order By: Relevance
“…This finding is in line with the literature that explores Black race as one of the most predictive factors for PTB. [54][55][56] In 14 studies, women were assessed on psychological measures more than once and repeated perinatal screening suggests an appreciation that mental health status during pregnancy is not static. It can be argued that measuring depression in early pregnancy may not be an accurate predictor because the development of subsequent depression might go undetected.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with the literature that explores Black race as one of the most predictive factors for PTB. [54][55][56] In 14 studies, women were assessed on psychological measures more than once and repeated perinatal screening suggests an appreciation that mental health status during pregnancy is not static. It can be argued that measuring depression in early pregnancy may not be an accurate predictor because the development of subsequent depression might go undetected.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The majority of research has found that between 3% and 9% of women experience abuse during pregnancy, 7,8 though there are well established risk factors that are associated with higher rates of abuse, including young age, single relationship status, minority race/ethnicity, and poverty. 9,10 Indeed, studies conducted among samples of low-income, predominantly single women have noted higher prevalence with rates up to 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the association of ethnicity to PTB was mediated through lower levels of personal resources, language barriers, economic difficulties, separation from friends and family, racial and neighbourhood discrimination for migrants (Coussons-Read et al, 2012;Rini et al, 1999;Ruiz et al, 2012), which all present an important area for future investigations. This finding is in line with the literature that explores Black race as one of the most predictive factors for PTB (Giurgescu, McFarlin, Lomax, Craddock, & Albrecht, 2011;Graham, Frank, Zyzanski, Kitson, & Reeb, 1992;Kiely et al, 2011). In 14 studies, women were assessed on psychological measures more than once and repeated perinatal screening suggests an appreciation that mental health status during pregnancy is not static.…”
Section: Discussionsupporting
confidence: 82%